2011
DOI: 10.1186/1748-5908-6-111
|View full text |Cite
|
Sign up to set email alerts
|

What implementation interventions increase cancer screening rates? a systematic review

Abstract: BackgroundAppropriate screening may reduce the mortality and morbidity of colorectal, breast, and cervical cancers. However, effective implementation strategies are warranted if the full benefits of screening are to be realized. As part of a larger agenda to create an implementation guideline, we conducted a systematic review to evaluate interventions designed to increase the rate of breast, cervical, and colorectal cancer (CRC) screening. The interventions considered were: client reminders, client incentives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 74 publications
7
109
1
1
Order By: Relevance
“…Numerous strategies exist to improve screening rates for colorectal and breast cancer, 2,3,5,6,[11][12][13][14][15][16][17][18][19][20] but the relative incremental benefit of these interventions have not been compared. 5 Using a pragmatic randomized trial, we examined the incremental benefit of several strategies to augment the effect of a patient reminder letter to improve cancer-screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous strategies exist to improve screening rates for colorectal and breast cancer, 2,3,5,6,[11][12][13][14][15][16][17][18][19][20] but the relative incremental benefit of these interventions have not been compared. 5 Using a pragmatic randomized trial, we examined the incremental benefit of several strategies to augment the effect of a patient reminder letter to improve cancer-screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prior studies have demonstrated that a letter alone increased screening rates for BC by approximately 4.5-9 % and for CRC by 0.2-10.9 %. 2,3 More recently, several studies have examined the benefit of multimodal interventions, including the RRO model to remind patients and providers when screening is due, recall unscreened patients, and implement culturally appropriate outreach to patients in need of screening. [4][5][6] Although multifaceted interventions have been shown to improve cancer-screening rates, 5-7 the relative incremental impact of the specific components of these interventions have not been fully assessed.…”
Section: Introductionmentioning
confidence: 99%
“…he use of incentives has become an increasingly popular means to entice positive changes in health behavior [31]. Although incentives show promising results in their eicacy in promoting preventive care activities, they have been shown to work best in highly structured environments when coupled with client reminders, and tends to promote behavior change only in the short term (32)(33)(34)(35). Very little evidence exists on the gender diferences in response to incentives, but some studies have shown that men tend to respond better when the incentive is monetary and of greater value [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Creating awareness: Various implications may be used in order to create awareness in the individuals about the importance of their protective behaviors in the prevention of CRC and their health. Evidence-based interventions recommended in the recent relevant studies are shown in Table 5 [10,25,[39][40][41][42][43][44]. Due to purpose of encouraging individuals take action to protective behaviors, it is important to give positive messages in materials (e.g., posters, banners) that it is possible to protect against CRC [11,36,37].…”
Section: Application Phasementioning
confidence: 99%
“…While facilitating effective participation in CRC screening initiatives, such as reminders, mass media and the media, group training, personal training, and assessments, are taken by reducing structural barriers to healthcare professionals and include initiatives such as feedback. The effectiveness of personal reminders, personal training, and counseling in improving CRC screening has been proven [10,25,[39][40][41][42][43][44]. Creating awareness: Various implications may be used in order to create awareness in the individuals about the importance of their protective behaviors in the prevention of CRC and their health.…”
Section: Application Phasementioning
confidence: 99%